An Optical Measuring Transducer for a Micro-Opto-Electro-Mechanical Micro-g Accelerometer Based on the Optical Tunneling Effect; Micromachines; Vol. 14, iss. 4 - Barbin E. S. Evgeny Sergeevich; Nesterenko T. G. Tamara Georgievna; Koleda A. N. Aleksey Nikolaevich; Shesterikov E. V. Evgeny Viktorovich; Kulinich I. Ivan; Kokolov A. A. Andrey Aleksandrovich (2023, 2023)
Title screen